2016
DOI: 10.1002/ajh.24408
|View full text |Cite
|
Sign up to set email alerts
|

Are we missing the mark? Fever, respiratory symptoms, chest radiographs, and acute chest syndrome in sickle cell disease

Abstract: Acute chest syndrome (ACS) is defined as a new pulmonary infiltrate detected by chest radiography (CXR) associated with fever, respiratory symptoms, or chest pain [1,2]. It is the second most common cause of hospital admissions in SCD, and can lead to significant morbidity and mortality [2]. Evidence in the literature has established that clinical assessment alone is not a sensitive predictor of ACS [1,2]. Although these studies were performed nearly 20 years ago, they advocate for empiric CXR utilization all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 5 publications
3
4
0
Order By: Relevance
“…As reported previously 20,21 , a higher WBC count at baseline predicted a higher risk of ACS and was also seen in our study. Furthermore, these patients demonstrated a further rise in WBC count associated with a considerable drop in haemoglobin from baseline and with significantly higher platelet counts, as these patients more frequently progressed to ACS when compared to VOC patients in the control group.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…As reported previously 20,21 , a higher WBC count at baseline predicted a higher risk of ACS and was also seen in our study. Furthermore, these patients demonstrated a further rise in WBC count associated with a considerable drop in haemoglobin from baseline and with significantly higher platelet counts, as these patients more frequently progressed to ACS when compared to VOC patients in the control group.…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, fever, hypoxia, and abnormal lung findings on clinical examination at admission are significant predictors for evolving to full blown ACS 9 . These findings also reemphasize the observations made in other studies, including the corporative study on SCA and others 20,21 . Table 2.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“… 19 This current study found that a high percentage of the VTE patients had a history of ACS (82.4%), implying that it did predispose to the occurrence of VTE, and such patients suffered from ACS as a complication of PE. Furthermore, previous research has demonstrated that PE is considered to significantly predispose for ACS, with PE episodes developing during ACS, 25 which is again similar to these current observations. However, it is difficult to conclude (from the current data), whether PE is a cause or a consequence of ACS.…”
Section: Discussionsupporting
confidence: 90%
“… 18 It has been suggested that thrombosis-in-situ could be responsible for this striking difference and that PE may be an aetiological factor in SCA patients that develop respiratory symptom. 25 Pulmonary hypertension with tricuspid regurgitation jet velocity ≥2.5 m/s is linked to VTE. 26 Although, SCD is a hypercoagulable state, the contribution of VTE to an elevated tricuspid regurgitation velocity is unknown.…”
Section: Discussionmentioning
confidence: 99%